TAKSU DALAM DRAMATARI CALONARANG: SEBUAH KAJIAN ESTETIKA HINDU - Wirawan, Komang Indra (Widyadari: Jurnal Pendidikan, 2018)
The performance of the dramatic art of Calonarang belongs to sacred arts. In a sense, the dramatic Calonarang is always staged as a complement to the yajña ceremony. Until now the staging of Calonarang remains a complement to the yajña ceremony, and still retains its magical and sacred power. Although in its development, the dramatic performances of Calonarang have shifted. From the former catharsis to the profane. However, the dramatic performance of Calonarang until now still retains the spirit of taksu which has been a functional power of the staging functionally still remains a sacred art that comes into contact with magical power and taksu. The emergence of taksu is a spirit that brings implications for the strengthening of local beliefs, that Calonarang's performances are a way of humans sheltering from noetic power.